INSERSI NILAI-NILAI PENDIDIKAN ANTIKORUPSI MELALUI PENGEMBANGAN HIDDEN CURRICULUM DI MIN 1 BANYUMAS - Al-nur, Widya Rahmawati (Mozaic : Islam Nusantara, 2021)
The insertion or strengthening of anti-corruption values ​​is a step taken by the government to insert anti-corruption values ​​into subjects in schools. The goal is none other than to create an anti-corruption generation from an early age. Anti-corruption education is a strategic study that is guarded in today's educational institutions in Indonesia in particular. This study is a qualitative descriptive study using a phenomenological approach that describes the results of developing a hidden curriculum in order to strengthen or insert anti-corruption values ​​at MIN 1 Banyumas. Data collection techniques used are observation, interviews and documentation and data analysis using the Milles and Huberman model. In this study, the insertion of anti-corruption values ​​through the development of a hidden curriculum is manifested in several ways, namely, first, the insertion of anti-corruption values, namely by strengthening honesty, discipline, responsibility and cooperation in positive ways. Second, the hidden curriculum development model used is the grass-roots model, and the three activities that support the insertion of anti-corruption attitudes are activities designed by teachers including classroom cleaning competitions, procurement of self-development books and procurement of anti-corruption pins.